Mathswork 1 - Mills, Steve (Wayland, 1999)
This book presents the basics of maths, such as shapes, measurements and number, to children in a fun and enjoyable way. It covers the key parts of the National Curriculum for Mathematics at Key Stage I and has been designed specifically for use during the numeracy hour.